Do exílio a símbolo cultural : a construção do ícone "Santa Dica" em Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Despite an impact on the imaginary and collective memory, there was still no research that studied the construction of Santa Dica as a “cultural symbol”, that is, the formation of the discourse that made a simple woman from the interior of Goiás a “Santa”, a leader of the social movement or an exemplary figure for the feminist struggle, known throughout Brazil. These multiple images are perceived in the various academic studies on her, as the past is not unified and admits multiple interpretive possibilities, making Santa Dica presented as a revolutionary peasant, as a woman ahead of her time who seeks to extricate herself from a patriarchal and macho society or a charismatic leader who managed to convince a group of acolytes of her sacred character. One of the important questions to be answered by the research is how “Santa Dica”, initially object of veneration by the poorest layers, gradually became a “personality”, to the point of being an important cultural symbol of Goiás and of being known nationally in the cultured circles? We believe that the different images about Dica went through what they call “the process of heroization”, that is, the transformation of an ordinary individual or even despised at certain times into an individual who becomes an identity symbol of a people. This dissertation will be divided into three chapters: Santa Dica in academic production, Santa Dica in Exile (1926) and Santa Dica in cultural production.
from exile to cultural symbol : the construction of the icon “Santa Dica” in Goiás.
Keywords: Dica; santa; exílio; historiografia; cultura; Dica; saint; exile; historiography; culture; GEOGRAFIA::GEOGRAFIA HUMANA; CIENCIAS SOCIAIS APLICADAS